Terbangan Menara Kudus: Musical Style, Community Perceptions, and Cultural Adaptation amid Socio-Cultural Change - Muhammad Panji Wahyu Mukti; Syahrul Syah Sinaga; Eko Sugiarto (Mimbar Agama Budaya, 2026)
Traditional arts, such as Terbangan Menara in Kudus Regency, Indonesia, face both opportunities and challenges as a result of sociocultural shifts. This study looks at Terbangan Menara's musical style, community attitudes, and cultural adaptation in the face of sociocultural change. Twenty two purposefully chosen informants, including performers, cultural leaders, members of the community, young people, Yayasan Menara Makam Sunan Kudus (YM3SK) management, and regional cultural stakeholders, participated in a qualitative study. Interviews, observations, and documentation were used to gather data. The results demonstrate that Terbangan Menara maintains its own musical qualities while adjusting to modern advancements. It is distinguished musically by interlocking percussion harmonization, slow tempo changes from adagio to allegro, repeating ostinato rhythms in 4/4 meter, and a dramatic progression from mild to climax intensity. The vocal style employs harmonic minor and pentatonic melodic patterns performed collectively through sholawat chanting, accompanied by rebana instruments such as kemplong, telon, salahan, lajer, and jidur. The integration of Javanese rhythmic elements, Islamic lyrics, and call-and-response percussion reflects the acculturation of Islamic and Javanese traditions. Community perceptions are generally positive; however, modernization and changing youth entertainment preferences have reduced participation. Therefore, cultural education, youth involvement, musical innovation, and digital promotion are essential for sustaining Terbangan Menara as Kudus cultural heritage.